O plano de ações articuladas (par)como instrumento de gestão: estudo de caso do município de Itabaiana-se - Souza, Maria Da Conceição Ferreira; Parente, Cláudia da Mota Darós [UNESP] (My University, 2013)
The paper analyzes the Articulated Action Plan of the municipality of Itabaiana, in the state of Sergipe, for the period 2008 – 2011, by identifying the actions and sub-actions under the local government’s responsibility, as well as those actions depending on the support of the Brazilian Department of Education which have been fully implemented, partially implemented and not implemented. The analysis demonstrates the potential of the Plan as a management tool to assist the council in recognizing and systematizing the reality they live in, also making evident its limits as an instrument for triggering the actions and sub-actions prescribed.

O trabalho analisa o Plano de Ações Articuladas do munícipio de Itabaiana, estado de Sergipe, no período de 2008 a 2011, identificando as ações e subações de responsabilidade do município e aquelas dependentes da assistência técnica do Ministério da Educação, implementadas integralmente, em parte e não implementadas. A análise demostra as possibilidades do Plano como instrumento de gestão que auxilia o município no reconhecimento e na sistematização de sua realidade, porém evidencia limites do instrumento para o desencadeamento das ações e subações prescritas.

El trabajo analiza el Plan de Acciones Articuladas de la municipalidad de Itabaiana, en el estado de Sergipe, en el período de 2008 a 2011, e identifica las acciones y subacciones de responsabilidad de la municipalidad y las que dependen de la asistencia técnica del Ministerio de Educación, implementadas totalmente, parcialmente y no implementadas. El análisis demuestra las posibilidades del Plan como una herramienta de gestión que ayuda la municipalidad en el reconocimiento y en la sistematización de su realidad, pero muestra límites del instrumento para lograr el desencadenamiento de las acciones y subacciones prescritas.